2011
DOI: 10.1007/s11270-011-0851-4
|View full text |Cite
|
Sign up to set email alerts
|

Plant Availability and Uptake of Lead, Zinc, and Cadmium in Soils Contaminated with Anti-corrosion Paint from Pylons in Comparison to Heavy Metal Contaminated Urban Soils

Abstract: Red lead (Pb 3 O 4 ) has been used extensively in the past as an anti-corrosion paint for the protection of steel constructions. Prominent examples being some of the 200,000 high-voltage pylons in Germany which have been treated with red lead anti-corrosion paints until about 1970. Through weathering and maintenance work, paint compounds and particles are deposited on the soils beneath these constructions. In the present study, six such "pylon soils" were investigated in order to characterize the plant availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…Generally, the concentration and accumulation of this metal in plants are positively associated with the soil-soluble Cd fractions (Gao et al 2011 ). Availability of Cd to plants is related to pH, soil organic matter, and redox potential (Gao et al 2011 ; Brokbartold et al 2012 ; Kacálková et al 2014 ). Cadmium inhibits activity of photosynthetic enzymes, decreases chlorophyll content, increases membrane conductance, and causes oxidative stress, resulting in inhibition of photosynthesis and growth (Duchovskis et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the concentration and accumulation of this metal in plants are positively associated with the soil-soluble Cd fractions (Gao et al 2011 ). Availability of Cd to plants is related to pH, soil organic matter, and redox potential (Gao et al 2011 ; Brokbartold et al 2012 ; Kacálková et al 2014 ). Cadmium inhibits activity of photosynthetic enzymes, decreases chlorophyll content, increases membrane conductance, and causes oxidative stress, resulting in inhibition of photosynthesis and growth (Duchovskis et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Paints are one of the outstanding sources of lead in the environment [19] with the use of leadbased additives during paint manufacture as the major contributor to lead in paints [20]. However, the additives used in paint manufacturing contain not only lead but also other heavy metals [21].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the relatively moderate total Pb content of the three pylon soils, the Pb amounts extractable with NH 4 NO 3 are high, reaching almost 15% of total Pb in soil B. These high Pb NH 4 NO 3 -extractabilities and the respective high Pb plant uptake were already described and discussed by Brokbartold et al (2012a;2012b), coming to the conclusion that the assumed extremely low water solubility of red lead (Haynes, 2010) is apparently not valid in soil environments. The presence of anglesite in the anti-corrosion paint can be explained by Pb interacting with SO 4 2− in rainwater from SO 2 emissions (Sanusi et al, 1996).…”
Section: Discussionmentioning
confidence: 86%
“…Pb derived from red lead anti-corrosion paint is an exception since earlier studies have shown that Pb derived from red lead anti-corrosion paint represents a Pb source that provides substantial amounts of extractable and plant available Pb, even if (a) the total Pb soil content (150 to 750 mg kg −1 ) would normally cause no major concern in terms of plant uptake; (b) at soil pH around 5, whereby Pb contaminations from other sources are generally immobile and uncritical in terms of plant availability and uptake (Brokbartold et al, 2012a;Brokbartold et al, 2012b), but so far the reasons for this remain obscure. In a greenhouse experiment, the Pb uptake by loose-leaf lettuce plants cultivated on red-lead-paint-contaminated soil limed to neutral pH still resulted in Pb concentrations twice as high as the permissible level for leafy vegetables of the European Union of 0.30 mg kg −1 fresh weight (EC, 2006), although the total Pb soil content of about 350 mg kg −1 was relatively low (Brokbartold et al, 2012a). In plant experiments under field conditions using Italian ryegrass cultivated on red lead anti-corrosion paint-contaminated pylon soils the Pb content in the plant biomass exceeded the permitted maximum Pb-content in green fodder (30 mg kg −1 at a moisture content of 12%) defined in the EC directive 2005/87/EC (EC, 2005) in two soils by up to about 350% (Brokbartold et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%